Early Training on Risk Mitigation of Economic Losses Due to Natural Disasters in the Agricultural Business Sector in Tasikmalaya Regency - Sukono Sukono; Sri Purwani; Dewi Ratnasari; Titin Herawati; Sutiono Mahdi (International Journal of Research in Community Services, 2022)
Natural disasters are unexpected events caused by nature, including earthquakes, tsunamis, hurricanes, droughts, floods, volcanic eruptions, landslides and hurricanes. From the several examples of natural disasters above, of course there are a lot of losses in various fields, one of which is in agriculture, with the negative impacts that exist, there needs to be countermeasures to anticipate these negative impacts. One of the steps we can take after a natural disaster occurs to reduce these losses is to mitigate risks. Risk mitigation itself is breaking down (diversifying) into smaller risk parts, and forming an investment portfolio. At training this time, we as a team will provide counseling to MI Cipicung students entitled "Training in Mitigating the Risk of Economic Loss through Diversification and Insurance in the Agricultural Business Sector of Tasikmalaya Regency".